2012
DOI: 10.1007/s10964-012-9754-y
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Peer Pathways to Adolescent Delinquency: Variations by Ethnicity and Neighborhood Context

Abstract: Effects of ethnicity and neighborhood quality often are confounded in research on adolescent delinquent behavior. This study examined the pathways to delinquency among 2,277 African American and 5,973 European American youth residing in high-risk and low-risk neighborhoods. Using data from a national study of youth, a meditational model was tested in which parenting practices (parental control and maternal support) were hypothesized to influence adolescents' participation in delinquent behavior through their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 71 publications
6
91
0
5
Order By: Relevance
“…En este sentido, se demostró que el estilo democrático, además de ser el más frecuente, era el que más beneficiaba a los jóvenes, en térmi-nos de menores problemas internalizantes y externalizantes y mayor desarrollo positivo, satisfacción vital y autoestima. Estos resultados son congruentes con los de otras investigaciones, en los que se ha demostrado la mayor prevalencia del estilo democrático, comparada con la de los otros estilos (Hoeve, Dubas, Gerris, Van del Laan, & Smeenk, 2011;Oliva, et al, 2008;Torío, Peña, & Rodríguez, 2008;Wolfradt, Hempel, & Miles, 2003) y su beneficio en el ajuste adolescente a través de la prevención de delincuencia (Deutsch, Crockett, Wolff, & Russell, 2012;Hoeve, et al, 2011) y de la implicación en acoso escolar (Baldry & Farrington, 2005;Gómez-Ortiz, Del Rey, Casas, & OrtegaRuiz, 2014;Kawabata, Alink, Tsen, Van Ijzendoorn, & Crick, 2011), y el desarrollo de la autoestima (Alonso & Román, 2005), el rendimiento académico (Besharata, Azizia, & Poursharifib, 2011;Frey, Ruchkin, Martin, & SchwabStone, 2009), la competencia social y capacidad resiliente (Baumrind, 1991;Masten & Powell, 2003). Asimismo, los estudios realizados parecen sugerir la relación entre unas prác-ticas parentales coherentes con el estilo democrático y una mayor probabilidad de desarrollar un apego seguro (Cantón & Cortés, 2005), subyaciendo a esta última relación todos los beneficios adaptativos que se atribuyen a la generación de este tipo de apego.…”
unclassified
“…En este sentido, se demostró que el estilo democrático, además de ser el más frecuente, era el que más beneficiaba a los jóvenes, en térmi-nos de menores problemas internalizantes y externalizantes y mayor desarrollo positivo, satisfacción vital y autoestima. Estos resultados son congruentes con los de otras investigaciones, en los que se ha demostrado la mayor prevalencia del estilo democrático, comparada con la de los otros estilos (Hoeve, Dubas, Gerris, Van del Laan, & Smeenk, 2011;Oliva, et al, 2008;Torío, Peña, & Rodríguez, 2008;Wolfradt, Hempel, & Miles, 2003) y su beneficio en el ajuste adolescente a través de la prevención de delincuencia (Deutsch, Crockett, Wolff, & Russell, 2012;Hoeve, et al, 2011) y de la implicación en acoso escolar (Baldry & Farrington, 2005;Gómez-Ortiz, Del Rey, Casas, & OrtegaRuiz, 2014;Kawabata, Alink, Tsen, Van Ijzendoorn, & Crick, 2011), y el desarrollo de la autoestima (Alonso & Román, 2005), el rendimiento académico (Besharata, Azizia, & Poursharifib, 2011;Frey, Ruchkin, Martin, & SchwabStone, 2009), la competencia social y capacidad resiliente (Baumrind, 1991;Masten & Powell, 2003). Asimismo, los estudios realizados parecen sugerir la relación entre unas prác-ticas parentales coherentes con el estilo democrático y una mayor probabilidad de desarrollar un apego seguro (Cantón & Cortés, 2005), subyaciendo a esta última relación todos los beneficios adaptativos que se atribuyen a la generación de este tipo de apego.…”
unclassified
“…She concluded that microaggressions should be recognized as subtle discrimination that acts similar to overt discrimination and can evoke powerful emotional reactions and may affect mental health. Deutsch et al (2012) investigated the effects of ethnicity, parenting practices and neighborhood on adolescent delinquent behavior. Using a large sample of 2,277 African American and 5,973 European American youth residing in high-risk and low-risk neighborhoods.…”
mentioning
confidence: 99%
“…Questions, such as: "You know most of the people in your neighborhood" and "People in this neighborhood look out for each other" were answered in NEIGHBORHOOD EFFECTS ON HISPANIC YOUNG ADULT OUTCOMES 523 the form of "True" = 2 or "False" = 1 ratings. These items were based upon previously combined-item measurements of neighborhood cohesion (Deutsch, Crockett, Wolff, & Russell, 2012); however, the current study found that Cronbach's alpha increased by adding two additional items, such as: "On the whole, how happy are you with living in your neighborhood?" and "If, for any reason, you had to move from here to some other neighborhood, how happy or unhappy would you be?"…”
Section: Neighborhood Cohesionmentioning
confidence: 57%